Comparison of Financial Institution Supervision between Indonesia’s Danantara and Singapore’s Temasek Holdings - Suryana, Komang Genta; Astariyani, Ni Luh Gede; Sahadewa, Anak Agung Gde Ananta Wijaya (IJBLE Scientific Publications Community Inc., 2025)
This study examines a comparative analysis of financial institution supervision and state investment management between Indonesia and Singapore, focusing on the Indonesia Investment Authority (Danantara) and Temasek Holdings. The objective of this research is to identify the legal frameworks governing both entities and to analyze the fundamental differences in supervisory approaches, governance structures, and public accountability mechanisms. The research employs a normative juridical method using statute, conceptual, and comparative approaches, supported by the analysis of primary and secondary legal materials. The findings indicate that Indonesia applies a fragmented supervisory system in which the Financial Services Authority (OJK) and Bank Indonesia divide microprudential and macroprudential functions, while Danantara operates as a sovereign investment entity separate from the regulators. In contrast, Singapore adopts an integrated risk-based supervisory model through the Monetary Authority of Singapore (MAS) and establishes strategic synergy with Temasek Holdings, which is managed professionally under strong corporate governance principles, high transparency, and public accountability. The study concludes that Singapore’s model is more adaptive to global dynamics through the integration of supervisory functions and state asset management, whereas Indonesia needs to strengthen inter-institutional coordination, consistently implement risk-based supervision, and enhance the governance and transparency of Danantara. The Temasek model may serve as a reference for reinforcing Indonesia’s legal framework and improving the effectiveness of sovereign investment management.